Rancang Bangun Alat Sortir Bola Pingpong Berdasarkan Warna Bola Berbasis Mikrokontroler - Tri Ongko Priyono; Ilfani Yulianti; Slamet Purwo Santosa (JURNAL ELEKTRO, 2025)
The process of sorting ping pong balls based on color is an application that can be automated using microcontroller technology. This research aims to design and build a ping pong ball sorting tool based on the Arduino Uno ATmega328 microcontroller, which is capable of detecting and sorting balls based on color. This tool uses a TCS3200 sensor to identify the color of the balls and controls a servo motor that moves the balls to the appropriate sorting lane. The ping pong balls are inserted one by one, while the color reading and ball grouping are done automatically. The testing was conducted using 15 ping pong balls with 5 yellow balls, 5 green balls, and 5 orange balls. The test results showed that this tool, overall, has an accuracy rate of 96% in detecting and sorting balls according to color with an average time of 2 seconds per ball. Despite several external factors, the system was able to function effectively. This tool is expected to improve efficiency and accuracy in sorting ping pong balls and serve as a basis for further development in similar automated systems. Some errors occurred due to variations in light intensity and incorrect ball positioning, resulting in an overall error percentage of 4%.